Radiation Dose Modulation of Computed Tomography Component in Positron Emission Tomography/Computed Tomography. - Inoue, Yusuke (Seminars in Nuclear Medicine, 2022)
In oncology practice, the CT component of PET/CT may be used for attenuation correction, lesion localization, and CT diagnosis, and significantly enhances the clinical benefit of PET. However, acquisition of CT covering the whole body increases radiation dose and consequently the risk of cancer induction, and optimization should be pursued. In CT, radiation dose is a major determinant of image quality, and is mainly adjusted by modulation of tube current. Automatic exposure control (AEC) is widely used for tube current modulation, and increases tube current in a large patient and in strongly attenuating regions of a given patient to preserve image quality despite strong X-ray attenuation. Radiation dose determined by AEC depends on various factors, such as the type of AEC software, scout imaging direction, arm positioning, and patient centering. Because radiation dose reduction increases image noise and may degrade clinical utility, image quality should be assessed together with radiation dose in the process of optimization. Clinical demands for image quality vary largely depending on the aim of the CT component, with lower quality being sufficient for lesion localization than for CT diagnosis. Therefore, optimal radiation dose differs according to the aim. Determining optimal dose is a somewhat subjective and difficult task, and use of the diagnostic reference level, determined based on national or regional survey, is recommended to recognize need for optimization. The volume CT dose index and dose-length product are used as indices of CT radiation dose, and effective dose may also be calculated for comparison of stochastic effects among different radiation sources and among different imaging procedures. Wide coverage from the head to the lower extremities causes problems in estimating these indices in whole-body PET/CT. CT definitely enhances clinical benefits of PET but simultaneously increases potential detriments due to radiation exposure. In the era of hybrid imaging, nuclear medicine practitioners should be aware of the technology and radiation dose management of CT.